Pengaruh Price Discount dan Hedonic Shopping Motivation terhadap Impulse Buying Dimediasi Positive Emotion - Elsa Laura Rizky Barona; Muhammad Arif; Jufrizen Jufrizen (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This paper aims to determine the effect of price discount (x1), and hedonic shopping motivation (x2), on impulse buying (y) with positive emotion (z) as a mediating variable at UNIQLO in Medan City. This study used a quantitative approach by collecting data through questionnaires. The data analysis technique in this study uses a PLS-based SEM approach with SmartPLS 4.0. The population and sample of this study are all UNIQLO consumers in Medan City, totaling 96 people. The results of this study indicate that price discounts positively and significantly affect positive emotion, hedonic shopping motivation positively and significantly influences positive emotion, price discounts do not have a significant effect on impulse buying, hedonic shopping motivation positively and significantly influences impulse buying, positive emotion with a positive and significant influence on impulse buying, price discounts do not have a significant effect on impulse buying through positive emotion, and hedonic shopping motivation positively and significantly influences impulse buying through positive emotion.